(untitled) (E Conference Zone, 2024)
In this article, future primary school teachers are given ways to properly organize a lesson and some recommendations. Ways to develop the conditions for preparing future primary school teachers for constructive pedagogical activity are shown. Information about the imitative paradigm and its application to education is provided.